Evaluating dietary and behavioral impacts of commercial-type diets on the growth and anti-predator responses of Snake River cutthroat trout (Oncorhynchus clarkii behnkei) - Owens, Cheyenne Elizabeth, author; Myrick, Christopher A., advisor; Vieira, Nicole K. M., committee member; Angeloni, Lisa M., committee member (Colorado State University. Libraries, 2016)
Cutthroat trout (Oncorhynchus clarkii) are raised for restoration stocking and to provide boutique sport fishing opportunities. Because of limited cutthroat-specific culture information, cutthroat trout have been raised using diets and techniques developed for rainbow trout (Oncorhynchus mykiss), resulting in inconsistent growth performance. There is also evidence that intensive culturing may diminish anti-predator behavior in salmonids, which has not been tested in cutthroat trout. A brief overview of the state of cutthroat trout is described in chapter one of this thesis. The second chapter of this thesis describes a 6-month feeding trial conducted on juvenile Snake River cutthroat trout (Oncorhynchus clarkii behnkei) fed six different feed formulations. Two floating control diets were chosen for this study (Skretting Classic Trout and Skretting Steelhead), along with three floating commercial-type formulations with varying crude protein (CP) and crude lipid (CL) levels (40 CP:12CL, 45CP:16CL, and 45CP:24CL) and one floating experimental formulation (40CP:16CL diet with lysine, methionine and threonine balanced to match the 45CP:16CL diet – BFTC Experimental). Diet significantly (P<0.05) affected final average fish weight, with fish fed Skretting Steelhead, BFTC Experimental, and 45CP:24CL weighing significantly more than fish fed 40CP:12CL. Proximate composition was also altered by diet, with fish fed 45CP:24CL having significantly higher crude energy levels than fish fed 40CP:12CL and Skretting Classic Trout. In a simple cost analysis, it was found that the BFTC Experimental diet provided the lowest cost per pound of fish out of all diets. The results indicate that diets with greater than 40% protein and 12% lipid provide the greatest growth in juvenile Snake River cutthroat trout, and that amino acid balanced diets provide a cost efficient option for cutthroat trout growers. The third chapter of this thesis describes a study wherein fish from the diet study were divided into one of two different size classes (small [12 ± 2.5 cm TL], and large [20 ± 2.5 cm TL]) and observed during open field testing and during exposure to a novel avian predator model (great blue heron, Ardea herodias). Additional testing was run separately on a medium size class [16 ± 2.5 cm TL]. Small fish were significantly (P<0.05) less likely to freeze during open field tests than large fish and potentially more likely to dart (P=0.0652) than medium fish during simulated predator attacks. Significant differences in freezing response between small and large fish fed different diets were observed (P<0.05), with fish fed 45CP:16CL and BFTC Experimental showing a higher probability of freezing than fish fed Skretting Steelhead. Potential differences in darting response between medium fish fed different diets were also observed (P=0.0825), suggesting that differences in ingredients or ingredient inclusion levels between experimental and control diets had subtle effects on behavior. The results indicate that hatchery-reared cutthroat trout do exhibit anti-predator behaviors in response to a novel predator, however further research is necessary to determine if these behaviors differ from those exhibited by wild cutthroat trout.